Corporate governance reporting as a voluntary disclosure: A study on the annual reports of Square Group - Khan, Md. Habib-uz-Zaman; Ghosh, Suntu Kumar; Akter, Md. Shahriar (BRAC University, 2010)
Corporate governance refers to the manner in which a corporation is directed, and laws and customs affecting that direction. It includes the laws governing the formations of firms, the by-laws established by the firm itself, the structure of the firm The issue of corporate governance are receiving greater concentration in both developed and developing countries as a result of the increasing recognition that a firm’s corporate governance affects both its economic performance and its ability to access long term, low cost investment capital. The issue has been reinforced in the corporate sectors after the recent accounting scandals for companies like The Enrons, Worldcoms and the other companies. Nevertheless, this issue still remains almost unfamiliar in Bangladesh. The study focuses on a new trend introduced in the annual reports of one of the well-established business groups of Bangladesh. The paper involves empirical study as well as a questionnaire survey. The principal findings are twofold: firstly, we find that SQUARE makes very few disclosures on corporate governance on a voluntary basis. Secondly, we find that SQUARE user groups are in favor of such disclosures. However, the disclosures reported in Bangladesh by Square are not ample in achieving the goals of corporate governance.